Meningkatkan Hasil Belajar Siswa pada Pembelajaran Seni Tari dengan Menggunakan Metode Demonstrasi di Kelas VII SMP Pancasila - Ummul Husna Fitria; Yuliasma Yuliasma (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
Based on the results of observations of low learning outcomes in dance arts subjects caused by a lack of direct interaction between teachers and students where learning takes place using videos, a learning method is needed that can improve student learning outcomes. This study aims to describe the increase in learning outcomes by using a demonstration method in learning the art of dance in class VII SMP Pancasila. This research is a classroom action research conducted in two cycles, each cycle consisting of 4 stages, namely planning, action, observation, and reflection. The object of this study was 44 class VII B students of SMP Pancasila. The method used in data collection was a psychomotor test on 3 aspects, namely spatial aspects, time aspects, and energy aspects with instruments in the form of observation sheets of student learning activities. Data analysis uses the percentage formula. The results of this study indicate that in the first cycle, the average value obtained was 64% and increased in the second cycle by 95%. In the first cycle of student learning activities, the average student learning activity is 61% and in the second cycle is 82%. So it can be concluded that using the demonstration method in learning the art of dance in class VII Pancasila Middle School can improve students' psychomotor learning outcomes.